1975
DOI: 10.1037/0278-7393.1.6.736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual and tactual stimulus presentation on learning two-choice patterned and semirandom sequences.

Abstract: Three experiments compared the effects of visual and tactual stimulus presentation in two-choice sequential learning situations requiring a predictive response. In Experiments 1 and 2, subjects received a five-or six-unit repeating pattern; in Experiment 3, they received a semirandom sequence. Tactual as compared to visual stimulus presentation resulted in less trials to criterion in predicting a repeating pattern and in earlier frequency matching in predicting a semirandom sequence. These results suggest an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Likewise, studies of temporal pattern and rhythm discrimination also reveal modality differences (e.g., Collier & Logan, 2000;Garner & Gottwald, 1968;Glenberg & Jona, 1991;Handel & Buffardi, 1969;Manning, Pasquali, & Smith, 1975;Rubinstein & Gruenberg, 1971). When presented with rhythmic patterns of flashing lights or auditory stimuli, participants were much better at discriminating auditory as opposed to visual patterns (Rubinstein & Gruenberg, 1971).…”
Section: Modality Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, studies of temporal pattern and rhythm discrimination also reveal modality differences (e.g., Collier & Logan, 2000;Garner & Gottwald, 1968;Glenberg & Jona, 1991;Handel & Buffardi, 1969;Manning, Pasquali, & Smith, 1975;Rubinstein & Gruenberg, 1971). When presented with rhythmic patterns of flashing lights or auditory stimuli, participants were much better at discriminating auditory as opposed to visual patterns (Rubinstein & Gruenberg, 1971).…”
Section: Modality Constraintsmentioning
confidence: 99%
“…Vision may be more sensitive to initial items in a list (Beaman, 2002), whereas audition appears more sensitive to final list items (Crowder, 1986). Second, the auditory modality appears to have an advantage in the processing of sequential input, including low-level temporal processing tasks (Sherrick & Cholewiak, 1986) and pattern or rhythm discrimination (e.g., Manning et al, 1975). In a comprehensive review of the effect of modality on cognitive processing, Freides (1974) concluded that for complex tasks, audition is best suited for temporal processing, whereas vision excels at spatial tasks (for similar views, see also Kubovy, 1988;Mahar et al, 1994;Penney, 1989;Saffran, 2002).…”
Section: Modality Constraintsmentioning
confidence: 99%
“…In another experiment, also reported in Manning et al (1975), we found that tactually presented lateralized stimuli led to faster asymptotic probability matching than did visually presented lateralized stimuli.…”
mentioning
confidence: 69%
“…First, they are the only results that seem to show recency in this modality. Second, they appear to be part of the small group of tactual tasks for which performance is better or the same as in the visual modality (e.g., Handel & Buffardi, 1968Manning, 1977Manning, , 1978Manning et al, 1975).…”
mentioning
confidence: 99%
“…The purpose of this note is to announce the availability of an expository paper reviewing some combinatorial problems connected with the partitioning of sets of linear sequences on the basis of rotational equivalence (e.g., abc is equivalent ot bca and to cab). Interest in this problem aroused experimental work involving repeating serial patterns in different domains (e.g., Manning, Pasquali, & Smith, 1975;Vitz & Todd, 1969) and research illustrating the usefulness of studying the psychological equivalence of rotationally equivalent patterns (Handel, 1974).…”
Section: Visual Stimuli On a Relatively Slow Display Unit (Submitted mentioning
confidence: 99%